Investigation of the Possible Allostery of Koumine Extracted From Gelsemium elegans Benth. And Analgesic Mechanism Associated With Neurosteroids - Xiong, Bojun; You, Wenbing; Luo, Yufei; Jin, Guilin; Wu, Minxia; Xu, Ying; Yang, Jian; Huang, Huihui; Yu, Changxi (Frontiers in Pharmacology, 2021)
Translocator protein 18 kDa (TSPO) is an evolutionarily conserved 5-transmembrane domain protein, and has been considered as an important therapeutic target for the treatment of pain. We have recently reported the in vitro and in vivo pharmacological characterization of koumine as a TSPO positive allosteric modulator (PAM), more precisely ago-PAM. However, the probe dependence in the allostery of koumine is an important question to resolve, and the possible analgesic mechanism of koumine remains to be clarified. Here, we report the in vivo evaluation of the allostery of koumine when orthosteric ligand PK11195 was used and preliminarily explore the possible analgesic mechanism of koumine associated with neurosteroids. We find that koumine is an ago-PAM of the PK11195-mediated analgesic effect at TSPO, and the analgesic mechanism of this TSPO ago-PAM may be associated with neurosteroids as the analgesic effects of koumine in the formalin-induced inflammatory pain model and chronic constriction injury-induced neuropathic pain model can be antagonized by neurosteroid synthesis inhibitor aminoglutethimide. Although our results cannot fully clarify the allosteric modulatory effect of koumine, it further prove the allostery in TSPO and provide a solid foundation for koumine to be used as a new clinical candidate drug to treat pain.